miR-7 and miR-153 protect neurons against MPP+-induced cell death via upregulation of mTOR pathway - Fragkouli, Apostolia; Doxakis, Epaminondas (Frontiers in Cellular Neuroscience, 2014)
Differential expression of microRNAs (miRs) in the brain of patients with neurodegenerative diseases suggests that they may have key regulatory roles in the development of these disorders. Two such miRs, miR-7 and miR-153 have recently been shown to target α-synuclein, a protein critically involved in the pathological process of Parkinson’s disease. By using a well-established in culture Parkinson’s disease model that of neurotoxin 1-Methyl-4-Phenyl-Pyridinium (MPP+), we examined whether miR-7 and miR-153 display neuroprotective properties. Herein, we demonstrate that treatment of cortical neurons with MPP+ induced a dose-dependent cell death with apoptotic characteristics. This was reflected in altered intracellular signaling characterized by increased levels of activated kinases p38MAPK and ERK1/2 and reduced levels of activated AKT, p70S6K and SAPK/JNK. Overexpression of miR-7 or miR-153 by adenoviral transduction protected cortical neurons from MPP+-induced toxicity, restored neuronal viability and anti-apoptotic BCL-2 protein levels while attenuated activation of caspase-3. Moreover, both miR-7 and miR-153 interfered with MPP+-induced alterations in intracellular signaling pathways in a partially overlapping manner; specifically, they preserved activation of mTOR and SAPK/JNK signaling pathways in the MPP+-treated neurons, while miR-153 also attenuated MPP+-induced activation of p38MAPK. No major effects were observed in the rest of signaling cascades or proteins investigated. Furthermore, the neuroprotective effect of miR-7 and miR-153 was alleviated when MPP+ was co-administered with rapamycin. Taken together, our results suggest that miR-7 and miR-153 protect neurons from cell death by interfering with the MPP+-induced downregulation of mTOR signaling.